Causation mechanism analysis for haze pollution related to vehicle emission in Guangzhou, China by employing the fault tree approach. (May 2016) - Huang, Weiqing; Fan, Hongbo; Qiu, Yongfu; Cheng, Zhiyu; Xu, Pingru; Qian, Yu
Abstract: Recently, China has frequently experienced large-scale, severe and persistent haze pollution due to surging urbanization and industrialization and a rapid growth in the number of motor vehicles and energy consumption. The vehicle emission due to the consumption of a large number of fossil fuels is no doubt a critical factor of the haze pollution. This work is focused on the causation mechanism of haze pollution related to the vehicle emission for Guangzhou city by employing the Fault Tree Analysis (FTA) method for the first time. With the establishment of the fault tree system of "Haze weather—Vehicle exhausts explosive emission", all of the important risk factors are discussed and identified by using this deductive FTA method. The qualitative and quantitative assessments of the fault tree system are carried out based on the structure, probability and critical importance degree analysis of the risk factors. The study may provide a new simple and effective tool/strategy for the causation mechanism analysis and risk management of haze pollution in China. Graphical abstract: Highlights: FTA was employed for the causation mechanism of haze pollution related to vehicle emission in Guangzhou, China. Risk factors of the causation system of urban haze related to vehicle emission were discussed and elaborated. FTA was proved to be an effective tool for risk analysis and management of haze pollution related to vehicle emission.